Red Emissive Carbon Dot Superoxide Dismutase Nanozyme for Bioimaging and Ameliorating Acute Lung Injury - Liu, Cui; Fan, Wenbin; Cheng, Wen‐Xiang; Gu, Yiping; Chen, Yiming; Zhou, Wenhua; Yu, Xue‐Feng; Chen, Minghai; Zhu, Minrong; Fan, Kelong; Luo, Qing‐Ying (Advanced functional materials, 2023)
Harnessing the physiochemical properties and enzymatic activities of nanozymes will provide new insights for disease theranostics. Herein, a novel carbon dot (C‐dot) superoxide dismutase (SOD) nanozyme that exhibits red fluorescence with emission wavelength of 683 nm and shows high SOD‐like activity of >4000 U mg−1 is reported, which presents the great potential for imaging the biodistribution of nanozyme itself in vivo and ameliorating acute lung injury. Through surface modifications, the mechanism of C‐dot SOD nanozyme activity is revealed to be relied on their surface functional groups which bind with superoxide radicals, promote the electron transfer between C‐dots and superoxide radicals, and finally accelerate the dismutation of superoxide radicals. The absolute quantum yield of ≈14% of red fluorescence C‐dot nanozyme endow it bioimaging in vitro and in vivo. Moreover, the C‐dot nanozyme effectively enters the cells, accumulates at mitochondria, and protects living cells from oxidative damage by scavenging reactive oxygen species (ROS) and reducing the levels of pro‐inflammatory factors. Importantly, in vivo animal experiments demonstrate the accumulation of C‐dots in injure lung and therapeutic effect of C‐dot nanozyme toward acute lung injury in mice. The red fluorescent C‐dot SOD nanozyme shows great potential for in vivo bioimaging and management of ROS‐related diseases. Red emissive carbon dot nanozyme with high superoxide dismutase (SOD)‐like activity over 4000 U mg−1 is developed. The SOD nanozyme activity is revealed to be relied on their surface functional groups which capture O2•– and then promote the electron transfer between O2•– and π‐system of carbon dot. The C‐dot SOD nanozyme shows great potential in bioimaging and ameliorating acute lung injury.